RE-ORIENTATION OF WOMEN'S CAREER SELF-CONCEPT IN THE TRANSITION PERIOD OF MOTHERHOOD (British Journal of Global Ecology and Sustainable Development, 2024)
Many challenges are faced by women (housewives) who have careers outside the home, ranging from arranging schedules with their husbands and children to managing household chores efficiently. The purpose of writing this paper is to explore changes in women's self-conceptduring the transition to motherhood, focusing on how these changes affect aspects of identity and work-family life balance. A qualitative approach with in-depth interviews was used to explore a group of career women in education units who were undergoing a transition to motherhood. The data were analyzed using a thematic approach to identify four patterns of change:research indicates that career women experience a significant reorientation towards their self-concept during the transition to motherhood. These changes involve adjustments to career roles, reassessment of life priorities, and negotiating a balance between job responsibilities and motherhood.The re-orientation of career women's self-concept in the T period of motherhood marked a tipping point in a career woman's journey, where their self-concept underwent a substantial shift. The introduction of a new role as a mother requires careful adaptation and negotiation to the demands of work and family responsibilities. Awareness of these dynamics can support the development of policies and support programs for career women in facing these life transition challenges.